In vitro Antioxidant Activities and Polyphenol Contents of Seven Commercially Available Fruits - Basu, Paramita (Pharmacognosy Res, 2016)
BACKGROUND: Fruits are considered one of the richest sources of natural antioxidants. Their consumption has been linked to the prevention of oxidative stress-induced diseases. OBJECTIVE: In this study, in vitro antioxidant activities of blueberry, jackfruit, blackberry, black raspberry, red raspberry, strawberry, and California table grape extracts were evaluated. MATERIALS AND METHODS: Antioxidant activities were determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant potential (FRAP), 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS), nitric oxide (NO), superoxide anion (O(2)(−)) scavenging assays, and ferric reducing power. RESULTS: Black raspberry extract had the highest phenolic (965.6 ± 2.9 mg gallic acid equivalents [GAE]/g), flavonoid (186.4 ± 1.7 mg quercetin equivalents/g), and proanthocyanidin (2677 ± 71.1 mg GAE/g) contents. All fruit extracts exhibited increasing radical scavenging activities with increased concentrations. At 100 μg/ml, red raspberry extract showed the highest ferric reducing power (A(700) =0.3 ± 0.0052) and FRAP activity (A(593) =11.43 mM Fe(2+)/g). Black raspberry extract (100 μg/ml) exhibited the highest DPPH activity (A(517) =89.03 ± 0.0471). Jackfruit extract (100 μg/ml) had the highest ABTS (A(734) =35.6 ± 0.613), NO (A(540) =81.7 ± 0.2), and O(2)(−) radical scavenging (A(230) =55.5 ± 0.2) activities. Positive correlations were observed between IC(50) values for different radical scavenging activities and different polyphenolics. Red raspberry extract had the highest Pearson's coefficient values (0.952–1) between total phenolics, flavonoids, and proanthocyanidins and DPPH and superoxide radical scavenging activities. CONCLUSIONS: The antioxidant rich fruits in this study are good source of functional food and nutraceuticals that have the potential to improve human health. SUMMARY: All fruit extracts exhibited increasing radical scavenging activities with increased concentrations. Black raspberry extract is enriched in total phenols, flavonoids, and proanthocyanidins and showed the highest 2,2-diphenyl-1-picrylhydrazyl scavenging activity and red raspberry extract showed the highest ferric reducing power and ferric reducing antioxidant potential activity. Jackfruit extract exhibited the highest 2,2′azino-bis (3-ethylbenzothiazoline-6-sulfonicacid) diammonium salt, nitric oxide, O(2)- scavenging activities. Positive correlations were observed between IC50 values for different radical scavenging activities and different polyphenolics. [Image: see text] Abbreviations Used: Abs: Absorbance, ABTS: 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt, BHT: Butylated hydroxytoluene, DPPH: 2,2-diphenyl-1-picrylhydrazyl, DW: Dry weight, FRAP: Ferric reducing antioxidant potential, FW: Fresh weight, GAE: Gallic acid equivalents, NADH: β-nicotinamide adenine dinucleotide hydrate, NFL: The National Food Laboratories, NO: Nitric oxide, ONPG: ortho-nitrophenyl-β-galactoside, PBS: Phosphate buffered saline, PMS: Phenazine methosulfate, QE: Quercetin equivalents, ROS: Reactive oxygen species, SD: Standard deviation, SOD: Superoxide dismutase, TCA: Trichloroacetic acid, TPTZ: 2,4,6-tris(2-pyridyl)-s-triazine, Trolox: (±)-6-hydroxy-2,5,7,8-tetramethylchromane-2-carboxylic acid.